2022
DOI: 10.1097/pap.0000000000000380
|View full text |Cite
|
Sign up to set email alerts
|

Advances in Thyroid Pathology: High Grade Follicular Cell-derived Thyroid Carcinoma and Anaplastic Thyroid Carcinoma

Abstract: In the upcoming World Health Organization fifth edition classification of endocrine tumors, there were several major changes related to high grade follicular-derived thyroid carcinoma (HGFCTC) and anaplastic thyroid carcinoma (ATC) based on emerging evidence about the diagnostic criteria clinical behavior, prognostic factors, and molecular signatures of these tumors. In this review, we aim to summarize the major evolutions of HGFCTC and ATC. HGFCTC is a nonanaplastic carcinoma with high grade features (High mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 70 publications
(273 reference statements)
0
6
0
Order By: Relevance
“…Follicular thyroid tumours that do not show obvious signs of malignancy currently still require surgical excision and are judged to be benign or malignant based on the presence of envelope, vascularity, extrathyroidal tissue invasion and distant metastases [8]. However, studies have shown that only about 20%-30% of follicular thyroid tumours are proven to be malignant after surgery [9,10], meaning that most patients undergo diagnostic thyroid lobectomy despite the benign nature of the tumour, causing heavy emotional stress and financial burden to the patient. For this reason, it is urgent to have a non-invasive and effective method to predict the risk of benign and malignant thyroid follicular tumours and to guide the clinical diagnosis and treatment process.…”
Section: F Ollicular Thyroid Carcinoma (Ftc) Is the Second M O S T C ...mentioning
confidence: 99%
“…Follicular thyroid tumours that do not show obvious signs of malignancy currently still require surgical excision and are judged to be benign or malignant based on the presence of envelope, vascularity, extrathyroidal tissue invasion and distant metastases [8]. However, studies have shown that only about 20%-30% of follicular thyroid tumours are proven to be malignant after surgery [9,10], meaning that most patients undergo diagnostic thyroid lobectomy despite the benign nature of the tumour, causing heavy emotional stress and financial burden to the patient. For this reason, it is urgent to have a non-invasive and effective method to predict the risk of benign and malignant thyroid follicular tumours and to guide the clinical diagnosis and treatment process.…”
Section: F Ollicular Thyroid Carcinoma (Ftc) Is the Second M O S T C ...mentioning
confidence: 99%
“…This special issue of Advances in Anatomic Pathology highlights several hot topics in the realm of neuroendocrine neoplasia of the pituitary, thyroid, adrenal, parathyroid glands, and the pancreas; fundamental for the contemporary practicing pathologist's diagnostic arsenal. [1][2][3][4][5][6][7] These timely reviews will comprise current best practices, including algorithmic approaches to the diagnosis and grading of such entities, along with conveying essential advances at the molecular level. In addition, 1 review focuses solely on the newest updates in familial endocrine tumor syndromes.…”
mentioning
confidence: 99%
“…This review also acknowledges many of the pitfalls that we face, particularly in thyroid cytopathology, and highlights the importance of advances in molecular diagnostics that can aid our diagnostic abilities, particularly with limited fine needle aspiration samples that lack complete architectural structure and the presence or absence of invasive features to definitively classify a tumor as malignant or benign 3. Furthermore, Ghossein and Xu deliver a well-written overview detailing the advances in differentiating high-grade follicular carcinoma from anaplastic carcinoma with excellent illustrative examples comparing key histologic, immunohistochemical, and molecular features 4. This review is particularly helpful in demonstrating the key differences between poorly-differentiated and differentiated high-grade carcinomas and the molecular progression starting from a well-differentiated thyroid carcinoma to anaplastic transformation 4…”
mentioning
confidence: 99%
See 2 more Smart Citations